Urgensi Hukum Perdagangan Internasional Terhadap Sengketa Perdagangan Internasional Antara Indonesia-Amerika Serikat - Lutfia Azzahra; Rani Apriani (Fakultas Hukum Universitas Surabaya, 2023)
The present study aims to explicate the significance of the international trade laws in resolving the disputes arising between Indonesia and the United States. The export activity is a crucial aspect of a country's economy as it augments its foreign exchange earnings. Indonesia, being one of the largest exporters of the non-oil resource, i.e., shrimp, nonetheless, encounters impediments in its exports. The U.S. has accused Indonesia of endowing subsidies to exporters, thereby suppressing the prices of its commodities. The involvement of the WTO is indeed imperative in this regard as it is incumbent upon the organization to address the predicaments faced by its member states. This study employs the qualitative research method, wherein the researcher combines the acquired data as a reference for the research. This enables us to see how the portrayal of the importance of international trade law is formed to achieve agreements between nations and also to resolve various disputes that arise.